1989
DOI: 10.1021/ma00197a045
|View full text |Cite
|
Sign up to set email alerts
|

Solid-state CP/MAS carbon-13 NMR study of cellulose polymorphs

Abstract: Highly crystalline cellulose samples, which also have a high purity of crystal form, were used or prepared as models of cellulose polymorphs, cellulose I, III,, IV,, II, IIIn, and IVn, for solid-state 13C NMR and X-ray diffraction analyses. Differences between cellulose I, II, and III in the 13C NMR spectra appear at the chemical shifts of C6 in the anhydroglucose units; they have signals at 65.5-66.2, 63.5-64.1, and 62.1-62.8 ppm, respectively. Cellulose IV has a doublet signal for C4 at 83.6-84.6 ppm and a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

23
236
1

Year Published

1996
1996
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 386 publications
(260 citation statements)
references
References 7 publications
23
236
1
Order By: Relevance
“…Cellulose IV contributes peaks at chemical shifts similar to those for cellulose I, although the patterns of relative signal strengths are different (Isogai et al, 1989). The published data for cellulose IV cannot account for a peak at 62.0 ppm in Figure 9a.…”
Section: Crystal Formsmentioning
confidence: 81%
See 3 more Smart Citations
“…Cellulose IV contributes peaks at chemical shifts similar to those for cellulose I, although the patterns of relative signal strengths are different (Isogai et al, 1989). The published data for cellulose IV cannot account for a peak at 62.0 ppm in Figure 9a.…”
Section: Crystal Formsmentioning
confidence: 81%
“…10a) also showed a peak at 86.2 ppm, which was not present in the spectrum of apple cell walls (Newman et al, 1994). The narrow lineshape is consistent with a wellordered (crystalline) environment, but the chemical shift is not consistent with known crystalline forms of cellulose (Isogai et al, 1989). The peak is therefore tentatively assigned to well-ordered chains of noncellulosic substances, e.g.…”
Section: Crystal Formsmentioning
confidence: 95%
See 2 more Smart Citations
“…Spectrum 1 gave strong crystalline peak at 22.3° for (002) crystal plane and at 16.1° merged from peaks of (110) and (11 0) crystal plane, indicating a cellulose Ι crystalline structure for native cellulose (Focher et al, 2001;Oh et al, 2005). After dissolution with ultrasonic irradiation and regeneration, cellulose sample comprised mainly amorphous structure and little cellulose ΙΙ crystalline structure, suggested by a broad peak at 19.8° in the diffratogram (Isogai et al, 1989), as shown in spectrum 2. However, spectrum of sample 31 and 34 displayed three obvious crystalline peaks at 12.2°, 20.2° and 22.0°.…”
Section: Wide-angle X-ray Diffractionmentioning
confidence: 93%